(untitled) (Journal of Management and Social Sciences, 2018)
This study investigates the impact of fiscal policy on balance of payments adjustment in Nigeria within the periods, 1981-2015. Using the bound testing approach, the study established the relationship that exists among fiscal policy instruments (tax and government expenditure), investment, output and balance of payments adjustment in Nigeria. The result revealed that in the long-run, government spending, investment and outputs have positive impact on balance of payments adjustment in Nigeria. However, tax revenue had negative impact on balance of payments in Nigeria. The high deficit finance by the Nigerian government where government spending is greater than tax revenue in most of the years considered had sustained the current account surplus in the country. Therefore, expansionary policies on fiscal policy measures should be encouraged as they play vital role for the enhancement of balance of payments in Nigeria. Keywords Tax, government spending, investment, income, current account balance